Os valores da corrupção: administração de bens apreendidos e confiscados = The values of corruption: administration of seized and confiscated assets - De Oliveira Machado, Diogo (2017)
The article is dedicated to explore the touchable and untouchable values related to corruption. The research is inspired by reflections that international organizations – such as the United Nations, the Organization of American States, the World Bank and the Transparency International – have built to address the problem. Criminalists and internationalists who participate in these reflections engendered in international forums meetings delimit the theoretical framework of the article. The confiscation of property is a privileged strategy to respond to corruption, because it affects the profit, which is the main purpose of economic criminal activity. However, confiscation is only possible if provisional measures are previously adopted in order to preserve the value of goods while the trial reaches an end. The temporary constriction of these assets implies their custody by the State, who is responsible to manage them in a cost-effective way